Action Mechanism of Ginkgo biloba Leaf Extract Intervened by Exercise Therapy in Treatment of Benign Prostate Hyperplasia. (16th April 2013) - Peng, Chiung-Chi; Liu, Jia-Hong; Chang, Chi-Huang; Chung, Jin-Yuan; Chen, Kuan-Chou; Chou, Kuang-Yu; Peng, Robert Y.
Abstract : Benign prostatic hyperplasia (BPH), an imbalance between androgen/estrogen, overexpression of stromal, and epithelial growth factors associated with chronic inflammation, has become an atypical direct cause of mortality of aged male diseases. Ginkgo possesses anti-inflammatory, blood flow-enhancing, and free radical scavenging effects. Considering strenuous exercise can reduce BPH risks, we hypothesize Ginkgo + exercise ( Ginkgo + Ex) could be beneficial to BPH. To verify this, rat BPH model was induced by s.c. 3.5 mg testosterone (T) and 0.1 mg estradiol (E2) per head per day successively for 8 weeks, using mineral oil as placebo. Cerenin ® 8.33 μ L/100 g was applied s.c. from the 10th to the 13th week, and simultaneously, Ex was applied (30 m/min, 3 times/week). In BPH, Ginkgo alone had no effect on T, 5 α -reductase, and dihydrotestosterone (DHT), but suppressed androgen receptor (AR), aromatase, E2 and estrogen receptor (ER), and the proliferating cell nuclear antigen (PCNA); Ex alone significantly reduced T, aromatase, E2, ER, AR, and PCNA, but highly raised DHT. While Ginkgo + Ex androgenically downregulated T, aromatase, E2, and ER, but upregulated DHT, AR, and PCNA, implying Ginkgo + Ex tended to worsen BPH. Conclusively, Ginkgo or Ex alone may be more beneficial than Ginkgo + Ex for treatment of BPH.